THE EFFECT OF LIQUIDITY, CAPITAL INTENSITY, AND INVENTORY INTENSITY ON TAX AVOIDANCE - Urrahmah, Syifa; Mukti, Aloysius Harry (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to examine the effect of liquidity, capital intensity, and inventory intensity on tax avoidance with leverage and profitability as control variables. Tax avoidance was measured by Effective Tax Rate (ETR), liquidity was measured by current ratio, capital intensity was measured by capital intensity ratio, inventory intensity was measured by inventory intensity ratio, leverage was measured by Debt to Equity Ratio (DER), and profitability was measured by Return on Assets (ROA). The population in this study are all manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2017-2019. The sampling technique used is purposive sampling method and obtained as many as 106 data samples. The analytical method used is multiple linear regression.